Novel lipid-coated mesoporous silica nanoparticles loaded with thymoquinone formulation to increase its bioavailability in the brain and organs of Wistar rats - Heba M. Fahmy; Mostafa M. Ahmed; Ayman S. Mohamed; Engy Shams-Eldin; Taiseer M. Abd El-Daim; Amena S. El-Feky; Amira B. Mustafa; Mai W. Abd Alrahman; Faten F. Mohammed; Mohamed M. Fathy (BMC, 2022)
Abstract Aims The Blood-Brain Barrier (BBB) is a filter for most medications and blocks their passage into the brain. More effective drug delivery strategies are urgently needed to transport medications into the brain. This study investigated the biodistribution of thymoquinone (TQ) and the effect on enzymatic and non-enzymatic oxidative stress indicators in different brain regions, either in free form or incorporated into nanocarriers as mesoporous silica nanoparticles (MSNs). Lipid bilayer-coated MSNs. Materials and methods MSNs and LB-MSNs were synthesized and characterized using a transmission electron microscope and dynamic light scattering to determine the particle size and zeta potential. TQ encapsulation efficiency and TQ's release profile from LB-MSNs were also examined. The impact of loading LB-MSNs with TQ-on-TQ delivery to different brain areas was examined using chromatographic measurement. Furthermore, nitric oxide, malondialdehyde (MDA), reduced glutathione, and catalase were evaluated as oxidant and antioxidant stress biomarkers. Key findings The LB-MSNs formulation successfully transported TQ to several areas of the brain, liver, and kidney, revealing a considerable increase in TQ delivery in the thalamus (81.74%) compared with that in the free TQ group and a considerable reduction in the cortex (−44%). The LB-MSNs formulation had no significant effect on TQ delivery in the cerebellum, striatum, liver, and kidney. Significance TQ was redistributed in different brain areas after being encapsulated in LB-MSNs, indicating that LB-MSNs have the potential to be developed as a drug delivery system for selective clinical application of specific brain regions. Conclusions LB-MSNs are capable nanoplatforms that can be used to target medications precisely to specific brain regions